Viticulture in cold climate toward more sustainable wine production - Baraka Wadha, Noha (SLU/Dept. of Biosystems and Technology (from 130101), 2022)
This literature study investigates viticulture in a cold climate and how climate change could contribute to a more sustainable wine production. This study aims to investigate if wine production in cold climate regions could create a dynamic balance between productivity and the consumption of natural resources. The second aim is to identify the challenges and opportunities for a sustainable viticulture in cold climates concerning environmental, economic, and social dimensions. The results show that several factors affect viticulture productivity in cold climate countries such as climate factors (frost, high precipitation, short summer, temperature fluctuation), soil management, nutritional management, diseases, and production cost. Several sustainable challenges lead to environmental, social, and economic impacts. The use of fossil fuels, pesticides and chemical fertilizers can affect human health and the environment. There are good opportunities for building sustainable viticulture in a cold climate region by achieving the three dimensions of sustainability. In the environmental dimension practices such as site selection, an adaptation of new cultivars, mechanization, change of viticulture training system, good soil management, proper nutrition management, and the use of renewable energy should be applied. In the economic dimension improving energy and water efficiency (reducing cost), more sustainable training in agriculture and innovation, creating a new network in the supply chain to improve economies, and brand reputation are important. In the social dimension, cold climate viticulture would enhance local cooperation and communication, create local employment opportunities, promote healthy wine production that ensures respect for family standards, values, and beliefs, support local farmers, and promote worker health.